Identification of Transcription Factor Genes and Functional Characterization of PlMYB1 From Pueraria lobata - Shen, Guoan; Wu, Ranran; Xia, Yaying; Pang, Yongzhen (Frontiers in Plant Science, 2021)
Kudzu (Pueraria lobata) is a traditional Chinese food and medicinal herb that has been commonly used since ancient times. Kudzu roots are rich sources of isoflavonoids with beneficial effects for human health. To gain global information on the isoflavonoid/flavonoid biosynthetic regulation network in kudzu, de novo transcriptome sequencings were performed using two genotypes of kudzu with high and low isoflavonoid content in roots. RNAseq data showed that the genes of flavonoid biosynthetic pathway were significantly high represented in the up-regulated genes in the kudzu with high isolflavonoid content. To discover regulatory genes, 105, 112 and 143 genes encoding MYB, bHLH and WD40 transcription factors were identified and classified, respectively. Among them, three MYB, four bHLHs and one WD40 genes were found to be highly identical to their orthologs involved in flavonoid biosynthesis in other plants. Notably, the expression profiles of PlMYB1, PlHLH3-4 and PlWD40-1 genes were closely correlated with flavonoid accumulation profiles in different tissues and callus of kudzu. Over-expression of PlMYB1 in Arabidopsis thaliana significantly increased the accumulation of anthocyanins in leaves and proanthocyanidins in seeds, by activating AtDFR, AtANR, and AtANS genes. Our study provides valuable comparative transcriptome information for further identification of regulatory or structural genes involve in isoflavonoid pathway in P. lobata, as well as for bioengineering of bioactive flavonoid compounds.